An efficient and robust exfoliated bentonite/Ag3PO4/AgBr plasmonic photocatalyst for degradation of parabens. Issue 27 (22nd April 2020) - Ma, Jianchao; Yang, Shurong; Shi, Huixian; Pang, Jin; Zhang, Xiaopeng; Wang, Yuxing; Sun, Hongqi
Abstract : A mesoporous exfoliated bentonite (EB)/Ag3 PO4 /AgBr (30%) photocatalyst was designed to combine various functions to achieve efficient photodegradation of parabens. Abstract : Efficient visible-light-driven heterojunction photocatalysts have attracted broad interest owing to their promising adsorption and degradation performances in the removal of organic pollutants. In this study, a mesoporous exfoliated bentonite (EB)/Ag3 PO4 /AgBr (30%) photocatalyst was obtained by stripping and exfoliating bentonite as the support for loading Ag3 PO4 and AgBr. The particle size ranges of Ag3 PO4 and AgBr were about 10–30 nm and 5–10 nm, respectively. The exfoliated bentonite could greatly improve the dispersion and adsorption of Ag3 PO4 and AgBr, and significantly enhance the stability of the material during paraben photodegradation. 0.2 g L −1 methylparaben (MPB) was completely decomposed over the EB/Ag3 PO4 /AgBr (30%) in 40 min under visible light irradiation. In addition, the photocatalytic activity of EB/Ag3 PO4 /AgBr (30%) remained at about 91% after five recycling runs manifesting that EB/Ag3 PO4 /AgBr (30%) possessed excellent stability. Radical quenching tests revealed that holes (h + ) and hydroxyl radicals (·OH) were the major radicals. They attacked the side chain on the benzene ring of parabens, which were gradually oxidized to the intermediates, such as benzoic acid, 3-hydroxybenzoic acid, 4-hydroxybenzoic acid, azelaic acid, and eventually became CO2 and H2 O. The enhancement of photocatalytic activity and photo-stability could be ascribed to the stable structural characteristics, enlarged surface area, high absorption ability, and improved light absorption ability from loading Ag3 PO4 onto EB. Meanwhile, the matched energy levels of Ag3 PO4 and AgBr made the photoelectron–hole pairs separate and transfer effectively at the interfaces. As a result, the photocatalytic properties of EB/Ag3 PO4 /AgBr (30%) composites were enhanced.